Shellfish Collection and Community Connections in Eighteenth-Century Native New England. Issue 4 (October 2014) - Hunter, Ryan; Silliman, Stephen W.; Landon, David B.
Abstract: In recent years, the archaeology of Native American sites in colonial contexts has increased our understanding of how indigenous communities persisted in challenging times. Greater attention to practices helps to create a more enriched picture, especially when set in the context of food and consumption. This article considers shellfish remains excavated from three households on the Eastern Pequot reservation, located several kilometers Inland from the Connecticut coast in southern New England, to explore the role that shellfish gathering played in eighteenth-century subsistence and social practices in Native New England. Household variability in the specific species and quantity consumed, as well as disposal methods, provide insight into internal community decision making. Moreover, eighteenth-century reservation demographics strongly accentuate the role of women in the provision of these foodstuffs and in maintaining cultural connections to the coast and other off-reservation communities. Practices of gathering and consuming shellfish thus provide vectors of change and continuity in Native American communities of colonial New England, showing how these practices represent not only connections to a deeper past, but also ongoing and even resurging practices to engage with a colonial present.